2020
DOI: 10.15420/ecr.2019.09
|View full text |Cite
|
Sign up to set email alerts
|

Dual Antiplatelet Therapy in Coronary Artery Disease: Comparison Between ACC/AHA 2016 and ESC 2017 Guidelines

Abstract: Dual antiplatelet therapy (DAPT) is integral to the management of coronary artery disease (CAD) but there remains uncertainty as to the optimal approach for balancing an individual’s risk of atherothrombotic events versus their risk of bleeding complications. A myriad of clinical trials have investigated how factors such as antiplatelet selection or duration of treatment can affect outcomes in both stable CAD and acute coronary syndromes. To aid clinicians in the challenge of applying trial findings to the cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…After stent placement, dual treatment with a P2Y 12 inhibitor (such as clopidogrel, prasugrel or ticagrelor) and aspirin is recommended for ≥1 month in those in whom a bare metal stent was placed and ≥1 year after for those implanted with a drug-eluding stent. [ 84 ] Other major trials compared prasugrel or ticagrelor to clopidogrel on a background of aspirin and showed similar results for men and women. [ 83 , 85 , 86 ] Women made up approximately one-quarter of the population studied in these trials.…”
Section: Treatment Modalities For Secondary Prevention Of Cvdmentioning
confidence: 99%
“…After stent placement, dual treatment with a P2Y 12 inhibitor (such as clopidogrel, prasugrel or ticagrelor) and aspirin is recommended for ≥1 month in those in whom a bare metal stent was placed and ≥1 year after for those implanted with a drug-eluding stent. [ 84 ] Other major trials compared prasugrel or ticagrelor to clopidogrel on a background of aspirin and showed similar results for men and women. [ 83 , 85 , 86 ] Women made up approximately one-quarter of the population studied in these trials.…”
Section: Treatment Modalities For Secondary Prevention Of Cvdmentioning
confidence: 99%
“…The 2010 Expert Consensus from the American College of Cardiology Foundation/American College of Gastroenterology/American Heart Association (ACCF/ACG/AHA) stipulates that only patients at high risk of bleeding should receive PPI [ 7 , 8 ]. On the other hand, the 2018 ESC guidelines recommend routine use of PPI for all patients on DAPT [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…Clinicians have become wary of balancing the bleeding risks associated with DAPT with the risk of stent thrombosis plus other major adverse cardiovascular and cerebrovascular events (MACCE) [ 7 ]. Gastrointestinal bleeding, particularly upper gastrointestinal bleed (UGIB), is one of the most common serious bleeding adverse effects of antiplatelet therapy, which has led to the concurrent prescription of proton pump inhibitors (PPIs).…”
Section: Introductionmentioning
confidence: 99%
“…ASA and P2Y 12 inhibitors are commonly prescribed antiplatelet drugs for the secondary prevention of major adverse cardiovascular events. 27,28 Platelet inhibition with ASA did not show a significant effect on CCL5 release from convulxinactivated platelets, whereas CCL5 release after thrombin activation was reduced (►Fig. 3A).…”
Section: Single or Dual Antiplatelet Therapy Influences Ccl5 And Cxcl4 Releasementioning
confidence: 99%